Renoprotective effects of febuxostat compared with allopurinol in patients with hyperuricemia: A systematic review and meta-analysis - Sollip Kim; Hyun-Jung Kim; Hyeong-Sik Ahn; Se Won Oh; Kum Hyun Han; Tae-Hyun Um; Chong-Rae Cho; Sang Youb Han (The Korean Society of Nephrology, 2017)
Background: Hyperuricemia is reported to be related to rapid progression of renal function in patients with chronic kidney disease (CKD). Allopurinol, a uric acid lowering agent, protects renal progression. However, it is not widely used in patients with CKD because of its serious adverse event. Febuxostat can be alternatively used for patients who are intolerable to allopurinol. We aimed to determine renoprotective effect and urate-lowering effect between the two drugs. Methods: We performed a systematic review and meta-analysis of randomized controlled trials to assess the effects of febuxostat compared to allopurinol in patients with hyperuricemia. MEDLINE, Embase, and Cochrane Library databases were searched to identify research publications. Results: Four relevant publications were selected from among 3,815 studies. No significant differences were found in the changes in serum creatinine from baseline between the febuxostat and allopurinol groups. Changes in estimated glomerular filtration rate (eGFR) were observed between the two groups at 1 month (mean difference 1.65 mL/min/1.73 m², 95% confidence interval [CI] 0.38, 2.91 mL/min/1.73 m²; heterogeneity χ² = 1.25, I² = 0%, P = 0.01); however, the changes in eGFR were not significantly different at 3 months. A significant difference did exist in the changes in albuminuria levels from baseline between the febuxostat and allopurinol groups (mean difference −80.47 mg/gCr, 95% CI −149.29, −11.64 mg/gCr; heterogeneity χ² = 0.81, I² = 0%, P = 0.02). A significant difference was also observed in the changes in serum uric acid from baseline between the febuxostat and allopurinol groups (mean difference −0.92 mg/dL, 95% CI −1.29, −0.56 mg/dL; heterogeneity χ² = 6.24, I² = 52%, P < 0.001). Conclusion: Febuxostat might be more renoprotective than allopurinol.